2007
DOI: 10.1063/1.2436851
|View full text |Cite
|
Sign up to set email alerts
|

Coupled ion temperature gradient and trapped electron mode to electron temperature gradient mode gyrokinetic simulations

Abstract: Electron temperature gradient (ETG) transport is conventionally defined as the electron energy transport at high wave number (high-k) where ions are adiabatic and there can be no ion energy or plasma transport. Previous gyrokinetic simulations have assumed adiabatic ions (ETG-ai) and work on the small electron gyroradius scale. However such ETG-ai simulations with trapped electrons often do not have well behaved nonlinear saturation unless fully kinetic ions (ki) and proper ion scale zonal flow modes are inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 16 publications
8
100
3
Order By: Relevance
“…It peaks at around within this range. This is fortunately the case as nonlinear couplings trigger an energy cascade towards longer wavelengths [39]. In the previous section, it was demonstrated that the filtering procedure did not affect the fluxes.…”
Section: Convergence Of Nonlinear Spectramentioning
confidence: 99%
“…It peaks at around within this range. This is fortunately the case as nonlinear couplings trigger an energy cascade towards longer wavelengths [39]. In the previous section, it was demonstrated that the filtering procedure did not affect the fluxes.…”
Section: Convergence Of Nonlinear Spectramentioning
confidence: 99%
“…In reality, however, turbulence at larger scales (neglected here) would generate a fluctuating background, which may act in a stabilizing way on the smaller ETG structures and thus limit their radial extent. 52,71,72 In order to model this stabilizing effect, we add a weakly sheared background flow, as discussed already in Sec. III C, where MTMs caused saturation problems for the case D simulations.…”
Section: F Contributions Due To Etg Turbulencementioning
confidence: 99%
“…To address this question, one would extend the validation methodology discussed so far to calculation of a local sensitivity map in which both R=L Ti and R=L Te are varied, from which a fluxmatching fractional gradient error vectorẼ z ¼ ðE LT i ; E LT e Þ could be calculated by determining the simultaneous values of R=L Ti and R=L Te which when input into the microturbulence model yield predictions of Q i and Q e that simultaneously match the power balance Q i and Q e results. While the computational resources needed to perform such an analysis using long-wavelength gyrokinetic simulations (to say, nothing of multiscale simulations which incorporate electron-scale ETG dynamics that likely contribute to Q e in many cases [65][66][67][68][140][141][142][143][144][145][146] ) over many conditions or discharges remain prohibitive for current-day computing platforms, such approaches will likely be feasible on next-generation exascale platforms. Moreover, such an approach, or even further generalizations to include matching of particle and momentum fluxes via additional variations of density and rotation gradients, is readily feasible now for most reduced turbulent transport models with fairly modest computing resources, and should be pursued further.…”
Section: E Using Flux-matching Gradients To Construct Validation Metmentioning
confidence: 99%
“…A third, even more computationally expensive avenue of approach would be to investigate the impact of multiscale simulations which self-consistently incorporate q e -scale ETG fluctuations into these q i -scale simulations. [65][66][67][68][140][141][142][143][144][145][146] Other research avenues are possible as well. However, for the goals of this paper, it should be clear how utilizing a variety of local validation metrics for multiple predicted quantities can be employed to test model fidelity and our physical understanding at a level not possible by earlier global metrics.…”
Section: Fluctuation Sensitivity Plots and Validation Metricsmentioning
confidence: 99%